Acupuncture treatment for Hashimoto's thyroiditis: An exploratory randomized controlled trial - Shanze Wang; Chao Yang; Weimei Zeng; Hongfang Tian; Shihao Du; Jiping Zhao (Integrative Medicine Research)
Background: Hashimoto's thyroiditis (HT) has a high incidence rate and unresolved clinical symptoms. Although Hand Yangming Meridian Penetrating Acupuncture has been used to treat thyroid diseases in China, there is no randomized controlled trial (RCT) on HT. Methods: This exploratory RCT aims to preliminarily evaluate the efficacy, safety, and feasibility of Hand Yangming Meridian Penetrating Acupuncture in the treatment of HT. Included subjects were randomly assigned to the acupuncture group and the waiting treatment group at a ratio of 1:1. Subjects in the acupuncture group received 16 weeks of acupuncture treatment, followed by a 16-week follow-up observation phase. Subjects in the waiting group received thyroxine supplementation for 16 weeks, followed by 16 weeks of compensation treatment. Serum thyroid peroxidase antibody (TPOab) and thyroglobulin antibody (TGab) levels were the main indicators, and Thyroid-Related Patient-Reported Outcome short form (ThyPRO-39), MOS Item Short Form Health Survey (SF-36), and Hospital Anxiety and Depression Scale (HADS) scores were also recorded. Results: In total, 58 subjects were included. After 16 weeks of treatment, there was no statistical difference in the changes in TPOab levels between the two groups, but the TGab level in the acupuncture group was significantly lower than in the waiting group (difference: −141.97 [95 % CI: −222.4 to −61.5], P = 0.011). Moreover, the total ThyPRO-39 and SF-36 scores were statistically different between the two groups (PThyPRO-39 < 0.001, PSF-36 = 0.005). There was no statistical difference in HADS between the two groups. Conclusions: Hand Yangming Meridian Penetrating Acupuncture may be safe and feasible for HT hypothyroidism to improve symptoms and reduce TGab levels. Trial registration: This trial was registered at Acupuncture-Moxibustion Clinical Trial Registry: AMCTR-IOR-19000308 (ChiCTR1900026830, https://www.chictr.org.cn/searchprojEN.html).